A theory of housing demand shocks - Zheng Liu; Pengfei Wang; Tao Zha (Federal Reserve Bank of Atlanta, 2019)
Aggregate housing demand shocks are an important source of house price fluctuations in the standard macroeconomic models, and through the collateral channel, they drive macroeconomic fluctuations. These reduced-form shocks, however, fail to generate a highly volatile price-to-rent ratio that comoves with the house price observed in the data (the "price-rent puzzle"). We build a tractable heterogeneous-agent model that provides a microeconomic foundation for housing demand shocks. The model predicts that a credit supply shock can generate large comovements between the house price and the price-to-rent ratio. We provide empirical evidence from cross-country and cross-MSA data to support this theoretical prediction.
Keywords: E21; E44; G21; 330; price-rent puzzle; heterogeneity; marginal agent; cutoff point; liquidity premium; price-to-rent ratio; collateral constraint